Output feedback synchronization of multiple robot systems under parametric uncertainties - Cicek, Elif; Dasdemir, Janset (SAGE PUBLICATIONS LTD, 2017)
In this paper, we propose a novel cooperative control scheme that solves the position synchronization problem of multiple robot manipulators, under parametric uncertainties, in the case when only position measurements are available. The synchronization controller, adaptation law and the filter that generates a velocity-related signal from the position tracking error are designed via a Lyapunov-based stability analysis. It is shown that the proposed method guarantees semi-global asymptotic convergence of the position synchronization error. The simulation results on five robot manipulators ensure the feasibility of the filter/controller mechanism.
Keywords: Cooperative control; synchronization; adaptive control; output feedback control; robot manipulator; Automation & Control Systems; Instruments & Instrumentation